Inovação do modelo de negócios e a criação de valor sustentável: um estudo em empresas da construção civil - Treptow, Igor Ceratti (2019)
The significant increase in environmental degradation due to the uncontrolled exploitation of natural resources and the increase of inequalities in society has resulted in the need to adopt sustainable practices by organizations in order to minimize the impacts arising from their processes. Considering this scenario, we sought to analyze how the innovations of the business model are associated with the creation of sustainable value in construction companies in the city of Santa Maria, Rio Grande do Sul, Brazil. The present work has both academic and practical relevance insofar as it contributes to a better understanding of the process of promoting sustainability in the construction industry, due to the relationship it seeks to establish among the innovations in the business model to make it sustainable proposed by authors such as Lüdeke-Freund (2010), Boons et al. (2013), Bocken et al. (2014), Schaltegger, Lüdeke-Freund and Hansen (2016) and Yip and Bocken (2018) and the sustainable value creation proposed by Hart and Milstein (2003, 2004). For this, a qualitative study of exploratory nature was carried out, using semi-structured interviews with managers of four construction companies in order to analyze which innovations are adopted to create sustainable value, both in economic, social and environmental aspects. The results show that of the four constructors analyzed, three started a movement towards sustainable development, through innovations capable of creating sustainable value. In contrast, the study revealed that one of the construction companies has no innovations related to sustainability and consequently is able to create only economic value. It was also possible to demonstrate that the main practices adopted are considered to be environmentally sound while bringing superior financial returns, mainly due to the reduction of costs and the increase of stakeholder legitimacy.